2018
DOI: 10.12973/iji.2018.11448a
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Teacher-Motivation

Abstract: The study aimed to provide an in-depth analysis of the internal and external causes that were influential towards job motivation of the teachers who were selected according to some success performance criteria for the institutions which is called science, art school where the gifted students are educated. The study was adopted as a qualitative research method and the case study was used. The data of the study were collected with semi-structured interviews. Content analysis method was used in analyzing the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
13

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 7 publications
1
36
0
13
Order By: Relevance
“…The teacher's enthusiasm is increasingly visible when connected with the future educational process by utilizing technology in the learning process. Teacher motivation is one of the success factors in achieving learning goals [22] [23] [24]. Motivation is encouragement from within to do something.…”
Section: Fig 1 the Graph Of Teacher Training Resultsmentioning
confidence: 99%
“…The teacher's enthusiasm is increasingly visible when connected with the future educational process by utilizing technology in the learning process. Teacher motivation is one of the success factors in achieving learning goals [22] [23] [24]. Motivation is encouragement from within to do something.…”
Section: Fig 1 the Graph Of Teacher Training Resultsmentioning
confidence: 99%
“…By referring to the working conditions, the teachers referred to a conducive classroom environment, adequate physical infrastructures and the opportunities to have their hard work recognised by all the school stakeholders as important. Boru [21] stated that teacher motivation is linked with teacher performance, which is influenced by the teachers' capacity to teach and their working conditions. Besides, 35% of the participants considered that they must receive an increase in their salary in order for them to be motivated to meet the new challenges of the reforms.…”
Section: List Three Ways How the Moehrtesr Can Help In Enhancing Yourmentioning
confidence: 99%
“…The working conditions of teachers impact on the quality of teaching [20]. Indeed, the motivation, capacity and work conditions of teachers are linked to their performance [21]. In the study carried out in Mauritius, Belle [3] found that poor physical working conditions, like ramshackle classrooms, lack of furniture and broken windows and non-standard teaching resources like a lack of textbooks, overhead projectors, audio-visual aids and computers are all de-motivating factors.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2016) believe that teacher training should be practice-oriented and more practical, with a flexible combination of theoretical and practical readiness. Readiness for educational activities involves orientation to personal-oriented learning, support for the creative development of students, cooperation, the desire for dialogue, and collective assessment of the results of joint activities (Beeka et al, 2014;Börü, 2018).…”
Section: Problem Statementmentioning
confidence: 99%